Kajian Faktor Fisik Lingkungan Kerja Yang Berhubungan Dengan Tingkat Kelelahan Pada Tenaga Kerja Di Unit Spinning IV PT. Sinar Pantja Djaja Semarang - Suliswati, Lilik; Setiani, Onny; Joko, Tri (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2007)
ABSTRACT : Background : Production process in a textile industry may cause adverse effect on health of workes. One adverse effect is from machines and working environment that may produce noise and hot environment that can give negative impact on worker. Noise and heat excess in working environment can cause fatigue and decrease productivity of worker. The research aim was to find out the physical environmental factor that cause fatigue on worker in unit of spinning IV PT. Sinar Pantja Djaja Semarang. Method : This research was an observational study with a cross sectional approach. Sample taken for this research were 45 worker. Data was taken by the measurement of noise intensity and ambient temperature in production room, fatigue measurement was taken with reaction timer. Data were analized by using pearson product moment correlation and multiple regression analysis. Result : This research showed that noise intensity average was measured 91.70 dB and average of ambient temperature was about 30.650C. Time reaction average to light stimulus before working was 218,48 millisecond, time average reaction to light stimulus after working was measured 412,78 millisecon.d. Result of statistical test showed that there was a significant correlation between noise intensity and fatigue level (p-0.005), ambient temperature and fatigue level (p-0.1222). The result of multiple linear Regression showed that noise intensity has correlation with fatigue. Conclusion To decrease the impact of noise on worker, workers need to wear hearing protective devices and take a rest outside the production room. It is suggested that silencer is needed to decrease noise intensity and a appropriate ventilation and exhaust fan must be installed to meet the standard of working area for industry. Drinking water with mineral suplementation must be added to the management program to decrease the impact of heat stress on workers. Keyword : noise intensity, ambient temperature, heat, time reaction , and fatigue level.